Negative Transfer of Native Language in the Process of Vocabulary Acquisition—Based on the Study of Xiangning NO.1Senior School - Zhang, Le (Advances in Social Sciences Research Journal, 2017)
In China, students from primary school to senior high school have studied lots of English words. However, despite great efforts of teachers and students, the effect of vocabulary learning is not satisfactory. The influence of negative transfer of mother tongue in English vocabulary learning cannot be ignored. Firstly, this paper introduced the background, purpose and significance of errors made by Xiangning NO.1Senior School students in the process of vocabulary acquisition. Then, the paper reviewed overseas and domestic status of negative transfer. Thirdly, the author designed an experiment and then classified and analyzed students’ errors according to the results of questionnaires and English tests. It turned out that they made highlighted errors in terms of part of speech, word meaning and lexical collocation. Finally, the author tried to make suggestions to reduce the impact of negative transfer on students’ word learning.